Die Kono-S-Anastomose in der Chirurgie des Morbus Crohn - Seyfried, Steffen; Post, Stefan; Kienle, Peter; Galata, Christian (Der Chirurg, 2019)
BackgroundRecurrent disease at the anastomotic site after bowel resection represents a major problem in patients with Crohn’s disease. In 2011, a new anastomotic technique (Kono-S anastomosis) was published, which as a functional end-to-end anastomosis creating a wide anastomotic diameter aimed to reduce the rate of recurrence after surgery.AimTo evaluate the Kono-S anastomosis with respect to early and late postoperative complications and recurrence rate after surgical intestinal resection in patients with Crohn’s disease at a university center.Patients and methodsAll patients with Crohn’s disease who underwent Kono-S anastomoses between June 2015 and December 2016 at the Department of Surgery, University Medical Centre Mannheim, were included in the study. After obtaining informed consent, patient data regarding surgery and hospital stay were recorded in a prospective database. Follow-up was carried out by structured telephone interviews including disease progression, medication and surveillance. Statistical analysis was performed using the Graph Pad Prism 7 software. Ethics board approval was obtained from the Medical Ethics Commission II of the Medical Faculty Mannheim, Heidelberg University, Mannheim, Germany (No. 2017-575N-MA).ResultsA total of 53 patients (32 female and 21 male) were included in this study. The median procedural time was 157 min. The median follow-up was 12 months (range 4-23 months). Of the patients 3 developed early postoperative complications with a Clavien-Dindo score ≥ III and 25 patients with or without symptoms were controlled by endoscopy and/or magnetic resonance imaging (MRI) and no anastomotic recurrence was detected. No endoscopic interventions were necessary and 16 patients were symptom-free with no further specific therapy or controls.DiscussionThe Kono-S anastomosis is a safe anastomotic method with low morbidity. In the early follow-up recurrence rates of Crohn’s disease at the anastomotic site were low. In the literature a reoperation rate of 5 % per year is given for patients with Crohn’s disease after intestinal resection, so that in the long-term observation a valid statement on recurrence rate is possible. A potential advantage of the morphological end-to-end configuration of the Kono-S anastomosis is the better endoscopic dilatation compared to a side-to-side anastomosis.ConclusionThe Kono-S anastomotic technique has a low morbidity. In the early follow-up observational period no recurrence occurred in the anastomosis area in this series. Long-term data must clarify whether this technique is advantageous with respect to this aspect in the long run.